2021
DOI: 10.1371/journal.pone.0255193
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the choice of delivery place in a rural area in Laos: A qualitative analysis

Abstract: Background Home delivery (HD) without skilled birth attendants (SBAs) are considered crucial risk factors increasing maternal and child mortality rates in Loa PDR. While a few studies in the literature discuss the choice of delivery in remote areas of minority ethnic groups; our work aims to identify factors that indicated their delivery place, at home or in the health facilities. Methods A community-based qualitative study was conducted between February and March 2020. Three types of interviews were impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Furthermore, rather than financial constraints, the delay in seeking care or the first delay that could lead to the mother's death was heavily influenced by certain social and cultural beliefs. Pregnant women's lack of empowerment, the influence of spiritual healers, a close relationship with traditional birth attendance, and medication misuse were all important factors in the delay in seeking care [18,29,[33][34][35]. It was also discovered a culture in some ethnic groups that may lead to maternal death, in which pregnant women had to go into a forest for their births, where births were performed by themselves or with the assistance of their husbands, and then spend three days afterwards [21].…”
Section: Factors Influencing Maternal Deathmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, rather than financial constraints, the delay in seeking care or the first delay that could lead to the mother's death was heavily influenced by certain social and cultural beliefs. Pregnant women's lack of empowerment, the influence of spiritual healers, a close relationship with traditional birth attendance, and medication misuse were all important factors in the delay in seeking care [18,29,[33][34][35]. It was also discovered a culture in some ethnic groups that may lead to maternal death, in which pregnant women had to go into a forest for their births, where births were performed by themselves or with the assistance of their husbands, and then spend three days afterwards [21].…”
Section: Factors Influencing Maternal Deathmentioning
confidence: 99%
“…It was also reported that the majority of rural mother deaths were caused by a lack of access to skilled birth attendance and unskilled and incorrect management of traditional birth attendance, as well as the consequences of birth-related complications being more prevalent among rural pregnant women managed by unskilled birth attendance [22,36,45]. Contrary to popular belief, wealthy pregnancies had higher demand for HIV testing, Syphilis testing, ultrasound screening, skilled birth attendance, high-quality antenatal care services, and institutional deliveries [17,33].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, approximately 42% of child deliveries were attended by healthcare providers at home, primary healthcare facilities, or hospitals. However, routine maternal and child health (MCH) reporting indicates that a significant number of mothers who die during childbirth do not have access to health services and give birth at home (Kawaguchi et al, 2021). This research received budget support from the Lancang-Mekong Cooperation Special Fund (People's Republic of China), contributing to improving the MCH system in Remote Areas Bordering Thailand-Lao PDR.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined aspects of socioeconomic status (SES) that are associated with deterrence of facility-based childbirth in low-income settings, but few have quantitatively examined contributory factors [9][10][11][12][13][14][15]. In Kenya, efforts to encourage more women particularly those from rural and low SES communities to give birth in health facilities -including free maternal health services, health education, and ease of facility access-have been implemented, yet some women still do not give birth in health facilities [16].…”
Section: Introductionmentioning
confidence: 99%